PENERAPAN CAKAP DIGITAL PADA UMKM ROTIKU ROTI NAEK MAK UCHU KELURAHAN TANJUNGPINANG TIMUR - Saputra, Eko Murti; Basyid, Abdul; Leindarita, Betty (Jurnal Pengabdian, Pembelajaran dan Pemberdayaan Ekonomi Masyarakat (JP3EM), 2024)
The aim of this service is to educate and disseminate information to MSME players regarding the use of digital marketing to improve the MSME economy during the Covid 19 pandemic. This service is provided to MSME Rotiku Roti Naek Mak Uchu. To overcome the problems that exist at Rotiku Roti Naek Mak Uchu MSMEs, our group will implement a program that includes: a) digital marketing strategy; b) understand the market, accessibility, types and features; and c) the importance of digital literacy in the market. The program will be implemented through methods such as outreach, interviews, and practicals